Integral Method Analysis of Electroabsorption Spectra and Electrophotoluminescence Study of (C4H9NH3)(2)Pbl(4) Organic-Inorganic Quantum Well - Kattoor, Vidya; Awasthi, Kamlesh; Jokar, Efat; Diau, Eric Wei-Guang; Ohta, Nobuhiro (My University, 2018)
Electric-field-induced changes in absorption and photoluminescence (PL) spectra and in PL decay profile have been measured for two-dimensional hybrid organic inorganic halide perovskite semiconductor, ((C4H9NH3)(2)Pbl(4)) (N1). Electroabsorption (E-A) spectra observed at room temperature and at a low temperature of 45 K were analyzed by assuming the Stark shift, and the magnitudes of the change in electric dipole moment and polarizability following photoexcitation were determined. The strong signal observed in the E-A spectra at 45 K was interpreted in terms of the weak absorption band which shows extremely large Stark shift resulting from the large change in polarizability following photoexcitation. Electrophotoluminescence spectra of this compound, that is, field-induced change in PL spectra, show that PL of N1 is quenched by the application of electric field. Field effects on PL decay profiles show that the quenching results both from the field-induced decrease of the population of the emitting state following photoexcitation and from the field-induced lifetime shortening caused by the enhancement of the nonradiative decay rate at the emitting state. At a low temperature of 45 K, two exciton emissions, each of which originates from different phase, appear, and both emissions are quenched by the applied electric field with different efficiencies from each other. It is also found that trap emissions observed at low temperature in the wavelength region longer than the sharp exciton bands show more efficient field-induced quenching than that of the exciton emissions, suggesting that energy transfer from the photoexcited state to trapped states is decelerated by the applied electric field.